2009
DOI: 10.1073/pnas.0911405106
|View full text |Cite
|
Sign up to set email alerts
|

Activation of innate and humoral immunity in the peripheral nervous system of ALS transgenic mice

Abstract: During injury to the nervous system, innate immune cells mediate phagocytosis of debris, cytokine production, and axon regeneration. In the neuro-degenerative disease amyotrophic lateral sclerosis (ALS), innate immune cells in the CNS are activated. However, the role of innate immunity in the peripheral nervous system (PNS) has not been well defined. In this study, we characterized robust activation of CD169/CD68/Iba1؉ macrophages throughout the PNS in mutant SOD1 G93A and SOD1 G37R transgenic mouse models of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
178
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(195 citation statements)
references
References 33 publications
15
178
2
Order By: Relevance
“…The major populations increased in ALS and aging were from monocyte and macrophage lineages. These changes are consistent with other studies that have found robust activation of these cells as part of the immune response during ALS disease progression and aging (Butovsky et al, 2012; Chiu et al, 2009; Galbavy et al, 2017; Kullberg, Aldskogius, & Ulfhake, 2001; Zondler et al, 2016). …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The major populations increased in ALS and aging were from monocyte and macrophage lineages. These changes are consistent with other studies that have found robust activation of these cells as part of the immune response during ALS disease progression and aging (Butovsky et al, 2012; Chiu et al, 2009; Galbavy et al, 2017; Kullberg, Aldskogius, & Ulfhake, 2001; Zondler et al, 2016). …”
Section: Resultssupporting
confidence: 91%
“…In presymptomatic SOD1 G93A mice, immune activation in the peripheral and central nervous system begins focally and becomes widespread after clinical onset (Alexianu, Kozovska, & Appel, 2001; Chiu et al, 2009; Hall, Oostveen, & Gurney, 1998). Macrophage activation in the peripheral nervous system occurs in parallel with microglial activation and T‐cell infiltration in the spinal cord (Chiu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next signs of impairment appear in the mitochondria and in the cellular transport system (Zhang et al, 1997, Warita et al, 1999, Williamson and Cleveland, 1999, Mattiazzi et al, 2002, Kieran et al, 2005, Damiano et al, 2006, De Vos et al, 2007, Bilsland et al, 2008, Nguyen et al, 2009, Bilsland et al, 2010, Li et al, 2010. The immune response is initiated next (Alexianu et al, 2001, Chiu et al, 2008, Gowing et al, 2008, Chiu et al, 2009. After this, denervation of the motor units and loss of maximal force begins (Kennel et al, 1996, Frey et al, 2000, Fischer et al, 2004, Hegedus et al, 2007, Hegedus et al, 2008, but the impairment of normal function in the mouse is subtle and onset of overt symptoms is several weeks off, even in the most severe models.…”
Section: Timeline Of Deficitsmentioning
confidence: 99%
“…These changes include reactive astrocytosis that can be seen many months before motor neuron degeneration (G85R) (Bruijn et al, 1997), and loss of glutamate transport and GLT1 protein expression before the onset of clinical disease or overt motor neuron degeneration (Howland et al, 2002). Similarly, increased astrocytes activation and expression of immune/inflammatory markers are hallmark of this pathology (Chiu et al, 2008;Chiu et al, 2009). Is the reduction in GLT1 protein in astrocytes significant?…”
Section: Amyotrophic Lateral Syndrome (Als)mentioning
confidence: 99%